The Impossibility of Liberal Secularism: Religious (In)tolerance, Spirituality, and Not-Religion - Crosson, J. Brent (2018)
This article re-thinks the problem of religious (in)tolerance by analyzing the 2015 deportation of three “Hindu priests” from a Caribbean nation for the practice of obeah. Defined popularly as “witchcraft” or “African tradition,” obeah was first criminalized as the alleged inspiration for the largest slave uprising of the eighteenth century British Caribbean. I argue that the recent deportations in a nation that constitutionally enshrines freedom of conscience foregrounds some of the foundational limits of liberal secularism. I trace a genealogy of liberalism to critique the secular ideal of the “freedom from difference.” I suggest that attempts to invoke “spirituality” as a more inclusive idiom for denigrated forms of “not-religion” such as obeah extend rather than eliminate these limits of liberal secularism. I close by drawing some parallels with anti-Muslim nationalism in the u.s. and suggest some ways of thinking about a trinary formation of religion, not-religion, and secular power in modern nation-states.
Keywords: Liberalism -- obeah -- anthropology of secularism -- religious (in)tolerance -- Caribbean and Latin America -- u.s. Islam -- freedom of religion -- colonialism